Finding location of fake and phantom source for source location privacy in wireless sensor network. (26th October 2020) - ; Roy, Pradeep Kumar; Singh, Jyoti Prakash
Wireless sensor network (WSN) has various advantages over wired networks and hence it has been an important area of research since years. Several issues of WSN such as energy, delay, routing, security have been addressed rigorously in the past researches. However, the issues of privacy is still grey zoned. In privacy, the issue of source location privacy (SLP) is critical for targeting and monitoring applications. Past works addressing the issue of SLP have used variants of fake and phantom sources, establishing the use of fake and phantom sources as a promising resource for SLP. Amid these, the selection of proper location of fake and phantom sources is still an issue which significantly impacts the privacy as well as other constraints of WSN. To fill this gap, we propose an algorithm to select the location of fake and phantom sources in the network in order to provide better privacy and energy trade-off in the network. Our approach uses the concept of geometry for selecting the location of fake and phantom sources. The experimental results confirm that the proposed algorithm gives a promising trade-off between privacy and other constraints such as energy and traffic.